AGGRESSIVE BUSINESS PRACTICE IN SERBIAN AND EUROPEAN LAW AND LEGAL PRACTICE - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Summary: Any trader's behavior that is inherently disturbing, involves coercion (even physical), or undue influence, violating the consumer's freedom of choice, leading him to make an economic decision he would not make - is considered aggressive business practice. Prior to the adoption of the European Directive on Unfair Business Practices in 2005, legal particularism prevailed in this area, and concluding contracts with the behavior of a trader which can be considered aggressive, fell almost exclusively under the provisions of civil law. After the adoption of the already mentioned Directive, there is a so-called maximum harmonization, which results in the direct transposition of its provisions into the positive legal regulations of the member states and candidate countries for EU membership. The Serbian legislator acted in this way in all laws on consumer protection from 2010 until today. In this paper, an analysis of the European normative framework is performed, as well as a comparative legal analysis of several legal systems, and a case law in their framework, too. Special emphasis was placed on Serbian law. In writing the article, the author was motivated by the fact that there are almost no articles on this specific topic in domestic legal doctrine, as well by the need to provide answers to some questions that consistently arise from almost a list of unanimous provisions on aggressive business practice in European law. Some of these doubts relate to the dilemma of whether the ban on aggressive business practices extends to so-called "business-to-business" relations, which is not common for the Directive, which protects, above all, consumers who are not professionally engaged in business, and does not have the experience of a trader, nor is he expected to have the standard of care expected of a person selling a product or providing a service. Then, the question arises whether the provisions on the prohibition of aggressive behavior in commercial relations protect the economic interests of conscientious companies that comply with regulations in relation to competitors who do not respect them, or is the exclusive object of protection - the consumer.Some dilemmas relate to the question of whether the prohibition of aggressive business practices towards consumers also applies to public entities whose activities include the sale or provision of services, ie to entities founded by the state, as well as to the doubt as to whether there is a measure of harassment that is considered „common“, given good business practices? It is inevitable, also, to rise a question about the fact that there is very small number of Serbian court decisions in this area - is the reason that in our country the level of consumer protection is raised to such a high level that there is no need to resort to protection mechanisms defined by law and the Law on Obligations, or is it something else? These are just some of the questions I have tried to answer in this article.